Covid-19 shocking global value chains - Peter S. Eppinger; Gabriel Felbermayr; Oliver Krebs; Bohdan Kukharskyy (Kiel Institute for the World Economy (IfW), 2020)
In early 2020, the disease Covid-19 caused a drastic lockdown of the Chinese economy. We use a quantitative trade model with input-output linkages to gauge the effects of this adverse supply shock in China on the global economy through international trade and global value chains (GVCs). We find moderate welfare losses in most countries outside of China, while a few countries even gain from the shock due to trade diversion. As a key methodological contribution, we quantify the role of GVCs (in contrast to final goods trade) in transmittingthe shock. In a hypothetical world without GVCs, the welfare loss due to the Covid-19 shock in China is reduced by 40% in the median country. In several other countries, the effects aremagnified or reversed for several countries. Had the U.S. unilaterally repatriated GVCs, the country would have incurred a substantial welfare loss while its exposure to the shock would have barely changed.
Keywords: F11; F12; F14; F17; F62; 330; Covid-19; quantitative trade model; input-output linkages; global value chains; supply chain contagion; shock transmission